2022
DOI: 10.1021/acsnano.2c08961
|View full text |Cite
|
Sign up to set email alerts
|

MXene-Enabled Self-Adaptive Hydrogel Interface for Active Electroencephalogram Interactions

Abstract: Human–machine interaction plays a significant role in promoting convenience, production efficiency, and usage experience. Because of the universality and characteristics of electroencephalogram (EEG) signals, active EEG interaction is a promising and cutting-edge method for human–machine interaction. The seamless, skin-compliant, and motion-robust human–machine interface (HMI) for active EEG interaction has been in focus. Herein, we report a self-adaptive HMI (PAAS-MXene hydrogel) that can activate rapid gelat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 55 publications
0
35
0
Order By: Relevance
“…As shown in Figure 4 a, the weight loss rate of NEH was bigger than that of HCEP at 40 °C, 10% humidity, and 65.4% of NEH remained after 24 h. Besides, 65.3% of NEH and 78.5% of HCEP remained at 20 °C, 20% humidity for 7 days ( Figure 4 b). As we all know, when water evaporates, the hydrogel cannot maintain the tight adhesion; which, results in instability at the skin–electrode interface to influence signal quality and stability [ 22 ]. In our experiments, although the weight of NEH decreased more quickly than that of HCEP, the results also exhibited a certain water retention performance of NEH owing to the added glycerin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 4 a, the weight loss rate of NEH was bigger than that of HCEP at 40 °C, 10% humidity, and 65.4% of NEH remained after 24 h. Besides, 65.3% of NEH and 78.5% of HCEP remained at 20 °C, 20% humidity for 7 days ( Figure 4 b). As we all know, when water evaporates, the hydrogel cannot maintain the tight adhesion; which, results in instability at the skin–electrode interface to influence signal quality and stability [ 22 ]. In our experiments, although the weight of NEH decreased more quickly than that of HCEP, the results also exhibited a certain water retention performance of NEH owing to the added glycerin.…”
Section: Resultsmentioning
confidence: 99%
“…Sun [ 21 ] reported a copoly(acrylate-acrylic acid) hydrogel electrode with excellent water-resistant, underwater adhesion and swelling resistance for application to human skin in the aquatic environment. Luo [ 22 ] presented an MXene-poly(acrylic acid) composite hydrogel electrode which can provide excellent skin compliance. However, these hydrogel-based dry electrodes commonly have relatively unstable and low-sensitive biosignals, due to their electron conduction and subsequently high skin–electrode impedance.…”
Section: Introductionmentioning
confidence: 99%
“…We further compared the advantages of our hydrogel with other research work in terms of GF and electrical conductivity, and the results showed the superior performance of PGC hydrogels (Fig. 3f) [26,43,47,49,61,[63][64][65][66][67][68][69][70][71]. In addition, we tested the response/recovery time (100/150 ms) of the hydrogel sensor during stretching and compared it with other reported work (Fig.…”
Section: Conductivity Of Supramolecular Hydrogel Electronic Skinmentioning
confidence: 88%
“…Luo et al developed an MXene based sensor that can effectively sense brain electrical signals. 157 The data generated from these electrodes were processed using the Long Short-Term Recurrent Neural Network (RNN) model. The specialty of these models is that they retain the important information and discard the unimportant ones.…”
Section: Computational Methods In Skin-like Mxene Electrodesmentioning
confidence: 99%